PERBANDINGAN HASIL BELAJAR SAINS SISWA YANG DIAJAR DENGAN PAKEM DAN YANG DIAJAR DENGAN MODEL KONVENSIONAL - Sudarto Sudarto (Bajang Institute, 2022)
This research was a quantitative study with a Randomized Control Group Only design which aimed to determine the comparison of Science learning outcomes of students taught using PAKEN model and student Science learning outcomes that were taught using conventional learning model. The population were all the grade 8th students of SMPN 3 Makassar. The sampling method is Simple Random Sampling. The research data was obtained by providing tests in the form of multiple-choice questions and essays. Data analysis techniques were by inferential analysis using an independent sample t-test. The results showed that tcount (9.58) > ttabel (1.67). Conclusion: the science learning outcomes of students taught with PAKEM model were better than the science learning outcomes of students taught with conventional models